Female caregivers. Education in equality - Goicoechea-Gaona, María Ángeles (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The objective of this article is to offer material for educational agents to meditate on the need that all human beings have to receive care, based on the reflection on the role of care,. The methodology used is qualitative from gender theory. Care concerns all people, even if they are not aware of the resources they require. Traditionally, these tasks have been carried out by women in an invisible way without remuneration or recognition. In conclusion, the theoretical reflection on care and its ethics leads to planning its inclusion in the school curriculum to assume and guarantee it throughout the population.